THE INFLUENCE OF PREDISPOSING FACTORS ON TAXPAYER COMPLIANCE WITH PBB-RURAL RURAL IN BALANGAN REGENCY - Mawardi, Rakhmad; Hidayat, Yusuf; Yunani, Ahmad (International Journal Political, Law, and Social Science, 2022)
Implementation of Law Number 28 of 2009 concerning Regional Taxes and Levies there is a Transfer of Rural Land and Building Taxes and Urban (PBB-P2) as a regional tax whose authority has been transferred since January 2014 to the Regional Government, in this case the City Government and Regency Government. This transfer of authority makes it a big responsibility for local governments to manage PBB-P2 receivables, which are still low, causing the collection process to not work well and causing the realization of tax collection which is currently increasing, causing receivables to increase, this is due to the low quality of local government regulations. and indicates that taxpayer compliance is not optimal, including in Balangan Regency. The problem of receivables related to taxpayer awareness is also influenced by several behavioral factors. This study aimed to determine the effect of one factor of behavioral theory that is predisposing factors on tax compliance of the UN-Urban Rural (PBB-P2) in Balangan. This research uses quantitative research and collection of PBB-P2 in the district. The data includes secondary data in the form of Report on the realization of Land and Building Tax for Urban and Office (PBB-P2) Balangan Regency in 2020 as well as primary data obtained through questionnaires related to predisposing factors. The results of the study show that predisposing factors consisting of knowledge and attitudes affect the compliance of PBB-P2 taxpayers in Paringin District where the formation of obedient behavior can be determined by the knowledge and attitudes of taxpayers.